Bacteremia Associated with Pressure Ulcers at Alyarmuk Teaching Hospital in Baghdad - Jassim, Nuha S.; Alash, Sameer Abdul ameer (Iraqi Journal of Science, 2020)
Fifty patients(24 female and 26 male)with pressure ulcersassociated with different diseasesand attending AL-yarmouk Teaching Hospital in Baghdad were selected in this study. The duration of sample collection was from March to December 2018. All blood samples collected from patients were submitted to a blood culturing technique to examine bacteremia. The results showed that12 blood bacterial isolates were obtained. The isolated bacteria were subjected to Vitek-2, which is an accurate identification technique. The results of the blood culturing technique revealed that 33.3% were Gram negative bacteria, while 66.6% were Gram positive. Diagnosis by Vitek-2 showed that 33.3% wereStaphylococcus spp. , 33.3% were Enterococcus spp. , 25.1% wereSerratiamarcescens and 8.3% comprised Acinetobacterbaumannii. The results of minimum inhibitory concentration (MIC)by Vitek-2showed that Trimethoprime –Sulfamethazole concentration at 320 µgwas the MIC for Acinetobacterbaumanni, while piperacilin, Ticarcillin, and Ticarcillin-Clavulanic acidat 128 µgwere the MIC for Serratia marcescens . Acinetobacterbaumanniishowed 100% resistance to all antimicrobial agents, while for the Serratiamarescenceresistancevalues were 54.55%, 54.55%, and 45.45% for isolate numbers 1, 2, and 3, respectively. Gram positive bacteria recorded NitrofurantionMIC of 256 µgagainst Staphylococcus epidermidisand Enterococcus spp., withboth species showinghigh resistance compared with the others which had a value of87.50%.